Beyond Energy Trade and Transport in a Reconnecting Eurasia - Pepe, Jacopo Maria (Energiepolitik und Klimaschutz. Energy Policy and Climate Protection,, 2018)
Jacopo Maria Pepe examines the rapid development of non-energy transport infrastructure in the broader Eurasian space. By doing so, the author considers the ongoing structural transformation of the Eurasian continent against the backdrop of deepening commercial interconnectivity in Eurasia into broader areas of trade, supported by the rapid development of rail connectivity. He frames this process in a long-wave historical analysis and considers in detail the geopolitical, geo-economic, and theoretical implications of deepening physical connectivity for the relationships among China, Russia, Central Asia, and the European Union. Contents Eurasia before Europe: Trade, Transport and Power Dynamics in the Early World System Shifting Trade Flows and Centers of Economic Power in 21st Century Eurasia: Toward a Rimland-Led Unified System Eurasian Transport Integration Beyond Energy: Geo-Economic Transformation and Geostrategic Response Target Groups Researchers, academics, and students in the fields of international political economy, international relations, history, geopolitics, transport and economic geography The Author Jacopo Maria Pepe is currently Associate Fellow at the German Council on Foreign Relations (DGAP) and Adjunct Professor at SAIS-Johns Hopkins University, Washington-DC. Previously he has worked as a research associate and lecturer at the Berlin Centre for Caspian Region Studies, Freie Universität Berlin.